A New Model of the Lifetime of Wireless Sensor Networks in Pure Water Communications (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Abstract—In this paper we present an a new model for thelifetime of wireless sensor networks used for underwatercommunications in pure water. The new model for powercommunications takes into consideration parameters such aspower consumption for the active mode, power consumption forthe sleep mode, power consumption for the transient mode,transmission period, transient mode duration, sleep modeduration, and active mode duration. The power communicationsmodel is incorporated in the life time model of wireless sensornetworks. The life time model takes into consideration severalparameters such as the total number of sensors, network size,percentage of sink nodes, location of sensors, the mobility ofsensors, power consumption when nodes move and the powerconsumption of communications. The new model for powerconsumption in communications shows more accurate resultsabout the lifetime of the sensor network in comparison withpreviously published results.